Ibn Khaldun’s Concept of Education in Relevance of National Education System - Rahmani, Annisa Nur; Abdussalam, Aam; Nuryani, Pupun (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Ibn Khaldun is one of the leaders of Islamic thinkers, better known as scientists and historians, but also can be classified into various specialties of scientific disciplines, such as statesman, juridical, sociologists, educators, even philosophers and clerics. His expertise in the field of education have received less attention, not many gave deep analysis of Ibn Khaldun's concept of education. He is a figure who has a strong ambition to science so many works he produced during his lifetime. One of his works is phenomenal Muqaddimah book. In the book discussed a wide range of social science began, culture, geography, politics, and even education. The purpose of this paper to describe the concept of education according to Ibn Khaldun which include: educational goals, students, teachers, methods, curriculum, and educational environment and its relevance to the Indonesian national education system. The method in this paper by using the method of analysis concepts with noninteractive qualitative approach using an analysis of the concept through an analysis of the document. So the results of this study Ibn Khaldun's thought critical education and humanist could become a reference for the development of education in Indonesia